2005
DOI: 10.1124/mol.104.008821
|View full text |Cite
|
Sign up to set email alerts
|

Subtype-Specific Affinity for Corticosterone of Rat Organic Cation Transporters rOCT1 and rOCT2 Depends on Three Amino Acids within the Substrate Binding Region

Abstract: The affinity of corticosterone to organic cation transporters (OCTs) is subtype-and species-dependent. For example, the IC 50 values for corticosterone inhibition of cation uptake by transporters rOCT1 and rOCT2 are ϳ150 and ϳ4 M, respectively. By introducing domains and amino acids from rOCT2 into rOCT1, we found that the exchange of three amino acids in the presumed 10th transmembrane ␣ helix is sufficient to increase the affinity of rOCT1 for corticosterone to that of rOCT2. Replacement of these amino acids… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
82
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 87 publications
(88 citation statements)
references
References 20 publications
6
82
0
Order By: Relevance
“…Similarly, Zolk et al (2009) reported that a set of structurally diverse cationic drugs were markedly more effective inhibitors of OCT2-mediated metformin transport than of MPP transport. These observations with OCTs, and those presented here for the interaction of selected ILs with the MATEs, support the view that ligand interactions with multidrug transporters can include close-order (competitive) interactions and distant (allosteric) interactions (Gorboulev et al, 2005). We suggest that rather than having a single unique binding site, the MATEs have a binding surface that permits spatially distinct interactions with structurally distinct ligands.…”
Section: Mate1supporting
confidence: 69%
See 3 more Smart Citations
“…Similarly, Zolk et al (2009) reported that a set of structurally diverse cationic drugs were markedly more effective inhibitors of OCT2-mediated metformin transport than of MPP transport. These observations with OCTs, and those presented here for the interaction of selected ILs with the MATEs, support the view that ligand interactions with multidrug transporters can include close-order (competitive) interactions and distant (allosteric) interactions (Gorboulev et al, 2005). We suggest that rather than having a single unique binding site, the MATEs have a binding surface that permits spatially distinct interactions with structurally distinct ligands.…”
Section: Mate1supporting
confidence: 69%
“…MPP is a comparatively amphiphilic, planar, heterocyclic ring compound. Given the characteristic multiselectivity of MATEs (Tanihara et al, 2007) and the potential of xenobiotic transporters to display kinetically complex interactions with substrates and inhibitory ligands (e.g., Gorboulev et al, 2005;Harper and Wright, 2013), we elected to establish the kinetics of MATE1-mediated transport of two structurally dissimilar OCs, namely, the tetra-alkylammonium compound TEMA and the fluorescent substrate NBD-MTMA (Fig. 1).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…It has been shown first that OCTs are able to mediate sodiumindependent electrogenic transport of organic cations in both directions across the plasma membrane (3, 17); second, that a nontransported competitive inhibitor can inhibit rat OCT2 (rOCT2) from either side of the plasma membrane, suggesting inwardly and outwardly facing orientations of the substrate binding site (31); third, that rOCT1 contains high-and lowaffinity binding sites for individual organic cations (11); and fourth, that rOCT2 mediates electrogenic uptake of the inorganic cation Cs ϩ with high selectivity over Na ϩ and K ϩ (24). Mutagenesis identified seven amino acids in rOCT1 that are involved in substrate binding (9,10,21). In a three-dimensional model of rOCT1 based on the structure of the inwardfaced conformation of LacY permease (1) these amino acids could be located within a large inward-open cleft (21).…”
mentioning
confidence: 99%